Analisis Pengukuran Kinerja Portofolio Optimal Pada Indeks LQ-45 dengan Model Korelasi Konstan - Putri, Riris Frishania; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2023)
An investment is putting in funds with the goal that it will generate a result in the future. In making investment decisions, investors are inseperable from the consideration of return-risk. The higher return from investors then making the higher risk that will be faced. Therefore, to minimized risk and maximized return, it is necessary to do portfolio analysis. The purpose research is to create an optimal portfolio and measure of performance of the optimal portfolio on LQ-45 index stocks. The results obtained indicate that portfolio A is the optimal of portfolio. The proportion of stocks included in the optimal portfolio are ITMG (68.2%) and MEDC (31.8%) with the expected return from optimal portfolio being 0.33% while the risk is 0.0229. Measuring the performance of each portfolio in a row is portfolio A of 0.093, portfolio B of 0.031, and portfolio C of 0.067. Performance measurement analysis on the optimal portfolio shows that portfolio A has superior performance compared to other portfolios.